Review on the pharmacology and chemical analysis of the olives / Ab Muib N. N., Hannis Fadzillah Mohsin, and Ibtisam Abdul Wahab - Ab Muib, N. N.; Mohsin, Hannis Fadzillah; Abdul Wahab, Ibtisam (Universiti Teknologi MARA, Negeri Sembilan, 2020)
Olive or Olea europaea is originated from Mediterranean and cultivated in different regions of the world. Each part of the plant has its own unique botanical description and gives a lot of benefits, either for biological or common uses. In this research, the pharmacological properties of O. europaea were studied via literature reviews. In the laboratory, the extraction of secondary metabolites from the dried leaves of O. europaea was followed by the chromatographic investigation. The biological uses of O. europaea and detection of the phenolics from olive leaves are highlighted. Specifically, oleuropein is the targeted compound worth to be further analyzed.